Maternal Cardiac Output and Fetal Doppler Predict Adverse Neonatal Outcomes in Pregnant Women With Heart Disease. Issue 11 (23rd November 2015) - Wald, Rachel M.; Silversides, Candice K.; Kingdom, John; Toi, Ants; Lau, Cathy S.; Mason, Jennifer; Colman, Jack M.; Sermer, Mathew; Siu, Samuel C.
Abstract : Background: The mechanistic basis of the proposed relationship between maternal cardiac output and neonatal complications in pregnant women with heart disease has not been well elucidated. Methods and Results: Pregnant women with cardiac disease and healthy pregnant women (controls) were prospectively followed with maternal echocardiography and obstetrical ultrasound scans at baseline, third trimester, and postpartum. Fetal/neonatal complications (death, small‐for‐gestational‐age or low birthweight, prematurity, respiratory distress syndrome, or intraventricular hemorrhage) comprised the primary study outcome. One hundred and twenty‐seven women with cardiac disease and 45 healthy controls were enrolled. Neonatal events occurred in 28 pregnancies and were more frequent in the heart disease group as compared with controls (n=26/127 or 21% versus n=2/45 or 4%; P =0.01). Multiple complications in an infant were counted as a single outcome event. Neonatal complications in the heart disease group were small‐for‐gestational‐age/low birthweight (n=18), prematurity (n=14), and intraventricular hemorrhage/respiratory distress syndrome (n=5). Preexisting obstetric risk factors ( P =0.003), maternal cardiac output decline from baseline to third trimester ( P =0.017), and third trimester umbilical artery Doppler abnormalities ( P< 0.001) independently predicted neonatal complications and were incorporated into a novel risk index in which 0, 1, and >1 predictor corresponded to expected complication rates of 5%, 30%, and 76%, respectively. Conclusions: Decline in maternal cardiac output during pregnancy and abnormal umbilical artery Doppler flows independently predict neonatal complications. These findings will enhance the identification of higher risk pregnancies that would benefit from close antenatal surveillance.